Motivasi Belajar Siswa SMA pada Pembelajaran Daring di Masa Pandemi Covid-19 - Cahyani, Adhetya; Listiana, Iin Diah; Larasati, Sari Puteri Deta (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2020)
Education system in Indonesia is experiencing new challenges due to the Covid-19 virus outbreak, which has caused the entire learning system in educational institutions to be transferred to online learning methods. The disruption in the learning process causes some changes to students which ultimately affect the motivation to learn. This research uses a quantitative approach, with the sampling technique used is accidental sampling. The population in this study were all high school students who took part in the process online learning. The analytical method used to analyze the data obtained in this study uses the Mann Whitney U analysis method. This type of research uses the foundation of learning motivation theory and aspects from Chernis & Goleman's theory (2011). The results of this study indicate that the significance value of Mann Whitney U is 0,000 which means the motivation to learn in students who take online or online learning in the midst of the pandemic situation of the Covid-19 virus is decreasing, because the significance value of 0,000 is less than 0.05 (p <0,05).